2009
DOI: 10.1007/s11060-009-9946-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcome of long-term glioblastoma survivors

Abstract: Extended survival of 3 or more years is rare in patients with glioblastoma (GBM) but is becoming more common. Clinical outcome has not been well studied. We reviewed GBM patients at Memorial Sloan-Kettering Cancer Center between 2001 and 2003 who were seen for two or more visits. Patient characteristics and long-term clinical outcomes were reviewed for patients who had survived 3 or more years following diagnosis. Thirty-nine (11%) of 352 GBM patients were identified as long-term survivors. Median survival was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 15 publications
3
41
1
2
Order By: Relevance
“…11 This is not a routine practice in our unit and generally in the NHS. To inform the parents of a child with NF1 that a 'brain tumour' has been found but no treatment is going to be given can be challenging news to cope with.…”
mentioning
confidence: 99%
“…11 This is not a routine practice in our unit and generally in the NHS. To inform the parents of a child with NF1 that a 'brain tumour' has been found but no treatment is going to be given can be challenging news to cope with.…”
mentioning
confidence: 99%
“…Furthermore, Hottinger and colleagues found that 85 percent of long-term survivors of GBM had at least one significant neurological deficit leading to a decline of the median Karnofsy Performance Scale (KPS) value from that at the time of initial diagnosis (from 90 to 70). This decline ultimately results in impaired day-today function (Hottinger, Yoon et al 2009). …”
Section: Economic Impactmentioning
confidence: 99%
“…Unfortunately the study had two limitations: firstly, due to dwindling numbers, only HRQOL data from the first year of follow-up was analyzed; secondly, neurocognitive function was not formally tested during follow-up. However, there is some preliminary evidence that glioblastoma patients who survive for more than 3 years may fare less well, with 85% having at least one significant neurologic deficit [31].…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%